Factors influencing production and reproductive performance of Frieswal cattle maintained at organized farm conditions - RATHEE, S K; GUPTA, A K; RAJA, T V; CHAKRAVARTY, A K (The Indian Journal of Animal Sciences, 2017)
The effect of certain genetic and non-genetic factors, viz. sire, month, year, age group, and service period on the first lactation production and reproduction traits of Frieswal cattle reared at organized farm under tropical condition was assessed. The records on first lactation production and reproduction performance of 1,225 Frieswal cattle spread over a period of 24 years (1988-2011) were used for the study. The first lactation traits were first lactation milk yield (FLMY), first lactation 305 day or less milk yield (FL305DMY), first lactation length (FLL), age at firstcalving (AFC), first service period (FSP), first dry period (FDP) and first calving interval (FCI). The genetic and non-genetic factors incorporated in the models for FLMY, FL305MY, FLL, AFC, FSP, FCI and FDP accounted for 31.34, 26.42, 70.60, 15.87, 21.82, 21.60 and 71.97% of total variations, respectively. The effect of sire, year of calving, first service period and age at first calving had highly significant effect on FLMY, FL305MY and FLL. Among the non-genetic factors, year and month had highly significant effect on all reproductive traits except the effect of month on FDP. The effect of farm was significant on FSP and FCI and not on AFC and FDP. The effect of FSP was significant on FDP. The overall least squares averages of AFC, FSP, FCI and FDP were 949.32±5.47, 153.26±3.79, 432.92±3.73, 127.17±1.43, respectively in Frieswal cattle. It was concluded that the first lactation reproduction traits were influenced by the year of birth/ calving. The overall least squares averages for FLMY, FL305 and FLL were 2920.86±47.07 kg, 2765.92±42.84 kg and 307.49±1.51 days, respectively.